EFEKTIVITAS MODEL PENGEMBANGAN RESEARCH AND DEVELOPMENT PERMAINAN BOLA TANGAN PADA PEMBELAJARAN PENJAS : SYTEMATIC LITERATURE REVIEW - Lesmana, Gianjar; Subroto, Toto; Rahmat, Alit (Jurnal Porkes, 2024)
This research aims to find out how effective the research and development development model is in handball games in physical education learning. This research was conducted using the systematic literature review (SLR) method. This research was also guided through several systematic review processes using PRISMA (preferred reporting items for systematic reviews and meta-analyses). The database used to search for literature is available on google scholar. Search for articles on this research within the last 12 years published in national journals that can be accessed openly (open access). This research focuses on the research and development model for handball games in physical education learning. The results of the data identification show that the research and development development model in handball games is very effective in learning physical education in terms of motor skills, increasing students' learning motivation and actively participating in physical education learning in handball games.